As exportações do setor agropecuário da região Sul do Brasil: uma aplicação do modelo gravitacional - Silveira, Daniel Claudy da (2014)
This study aims to analyze trade flows of the main products of the agricultural sector (soybean, tobacco and meat) exported by the Southern Region of Brazil, its main market destinations (Argentina, China, United States and European Union), through a gravity model for estimation of panel data, with the approach of ordinary least squares (OLS - pooled) in the period 2000-2012. Finally, the estimation of the gravity model results showed that the estimates follow the seminal works of economic literature, demonstrating that the flows of the agricultural sector of the Southern Region suffer negative influence of the distance between countries and, on the other hand, positively, in relation to mass population and the real exchange rate on trade flows between countries/regions considered in the analysis period.